POT1 mutation spectrum in tumour types commonly diagnosed among POT1-associated hereditary cancer syndrome families. Issue 10 (14th January 2020) - Shen, Erica; Xiu, Joanne; Lopez, Giselle Y; Bentley, Rex; Jalali, Ali; Heimberger, Amy B; Bainbridge, Matthew N; Bondy, Melissa L; Walsh, Kyle M
Abstract : Background: The shelterin complex is composed of six proteins that protect and regulate telomere length, including protection of telomeres 1 (POT1). Germline POT1 mutations are associated with an autosomal dominant familial cancer syndrome presenting with diverse malignancies, including glioma, angiosarcoma, colorectal cancer and melanoma. Although somatic POT1 mutations promote telomere elongation and genome instability in chronic lymphocytic leukaemia, the contribution of POT1 mutations to development of other sporadic cancers is largely unexplored. Methods: We performed logistic regression, adjusted for tumour mutational burden, to identify associations between POT1 mutation frequency and tumour type in 62 368 tumours undergoing next-generation sequencing. Results: A total of 1834 tumours harboured a non-benign mutation of POT1 (2.94%), of which 128 harboured a mutation previously reported to confer familial cancer risk in the setting of germline POT1 deficiency. Angiosarcoma was 11 times more likely than other tumours to harbour a POT1 mutation (p=1.4×10 −20 ), and 65% of POT1 -mutated angiosarcoma had >1 mutations in POT1 . Malignant gliomas were 1.7 times less likely to harbour a POT1 mutation (p=1.2×10 −3 ) than other tumour types. Colorectal cancer was 1.2 times less likely to harbour a POT1 mutation (p=0.012), while melanoma showed no differences in POT1 mutation frequency versus other tumours (p=0.67). Conclusions: These results confirm a role for shelterin dysfunction in angiosarcoma development but suggest that gliomas arising in the context of germline POT1 deficiency activate a telomere-lengthening mechanism that is uncommon in gliomagenesis.